Specific learning disorders and anxiety: a matter of school experience? - Chiappedi, Matteo; Baschenis, Ilaria M (Minerva pediatrica, 2016)
Specific learning disorders (SLDs) are a group of neuropsychological disorders which reduce a child's ability to read and/or write and/or use numbers. Internalizing disorders, and in particular anxiety, has been reported as a relatively common comorbidity in children with reading difficulties. We conducted this study in order to test if school experience (in terms of perceived support from the teacher) is associated with the development of anxiety. Twenty patients with SLDs (age: 8-13) were compared to 32 healthy subjects of the same age. All subjects filled the scale to measure anxiety derived from the Self-Administered Psychiatric Scales for Children and Adolescents (SAFA); results were compared using non-parametric statistics after verifying that scores were not normally distributed. Patients more often had a clinically significant level of anxiety (Mann Whitney U Test; P<0.001). We found a significant inverse correlation between a school experience perceived as positive and anxiety (Spearman's rho=- 0.925; P<0.001), while no significant correlation was found for sex, age, timeliness of diagnosis or time since diagnosis. Although these findings need to be confirmed in prospective studies, the role of school experience for children with SLDs seems highly relevant also for their psychological well-being.